Financial Performance Measurement Analysis of Shariah Commercial Banks in Indonesia Using Risk Based Bank Rating (RBBR) and Shariah Conformity and Profitability (SCNP) Methods - Ubaidillah (Wealth: Journal of Islamic Banking and Finance, 2022)
This research aims to determine the level of performance of Islamic Commercial Banks in Indonesia using the Risk Based Bank Rating (RBRR) and Shariahh Conformity and Profitability (SCnP) for the 2017-2019 period. The object of this research is a BUMN Shariah Commercial Bank. The technique used for this research is purposive sampling using descriptive quantitative method. This study describes the performance of Islamic Commercial Banks through two methods, namely the Risk-Based Bank Rating (RBBR) method which is seen from 4 aspects, namely Risk Profile, Good Corporate Governance, Earnings, and Capital. The second method is Shariahh Conformity and Profitability (SCnP) which is seen from the Shariahh Conformity variable with indicators of Islamic Investment Ratio, Islamic Income Ratio, and Profit-Sharing Ratio and Profitability variable with indicators of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin Ratio. The results showed that dwith the Risk-Based Bank Rating (RBBR) method, Islamic Commercial Banks are in a “Healthy” or “Good” condition. While the analysis using the Shariahh Conformity and Profitability (SCnP) method, shows that Islamic Commercial Banks are spread in three quadrants, namely URQ, LRQ, and ULQ.